PELATIHAN “CARA MENGAJARKAN OPERASI BILANGAN BULAT PADA SISWA SEKOLAH DASAR” DESA KEDUNG KENDO KECAMATAN CANDI - Soffil Widadah (STKIP PGRI Sidoarjo, 2018)
This community service program aims to address the problem of most difficult parents in accompanying children when learning to count on negative integer operations. One of the causes of the emergence of the problem is because parents do not understand the way how to teach it. This activity is done in 3 stages. In the first phase, observations are made to the program objectives to determine the delivery method of the training in accordance with the target conditions and situation. In addition, coordination with village officials for licensing issues as well as preparing various things related to activities. In the second stage of the implementation phase, training on how to operate the integers in elementary school students on the target. At the end of the stage, follow-up is a follow-up consultation or guidance for parents who wish to deepen their insights on how to teach integer operations to elementary school students. After all, activities carried out the proposer prepares the activity report